CHEMICAL EFFECTIVENESS TEST OF SHEET MASK PREPARATIONS FROM GRAPES (Vitis Vinivera) JUICE AS A MOISTURIZING - Sayyidah, Sayyidah (STIKes Kharisma Persada, 2024)
ABSTRACTMasks are the most widely used dosage form today and make the skin clean to the deep layers that can't be reached with just regular washing. One form of mask that is currently a trend in the world, especially in Asia, is a sheet mask. The purpose of the study was to identify the method of making sheet mask preparations from grape juice and to identify the effectiveness of sheet mask preparations made from grape juice. This study used an experimental method by testing the oranoleptic test, homogeneity test, pH test with concentration (0%,2%,4%,6%), irritation test with 15 volunteers, humidity test with 28 volunteers and carried out for 1 week. Based on the results of the research concentration (0%,2%,4%,6%). Organoleptic test, the higher the concentration, the paler purple smells of strawberry, homogeneity test for all homogeneous preparations, pH test with concentration (0%: 6.73),(2%: 5.26),(4%: 4.83),( 6%: 4,51), irritation test there was no redness and itching in 15 volunteers, the higher the humidity test the more moist the skin, (0%: 36,57),(2%: 37,57),(4%: 38.14),(6%: 40.57). Conclusion: the formulation of grape juice sheet mask preparation, namely grape juice, can make the skin moist. ABSTRAKMasker merupakan bentuk sediaan yang paling banyak digunakan saat ini dan membuat kulit menjadi bersih sampai pada lapisan bagian dalam yang tidak bisa dijangkau hanya dengan pencucian biasa. Salah satu bentuk masker yang menjadi trend pada saat ini di dunia khususnya di Asia adalah masker sheet. Tujuan penelitian Mengidentifikasi cara pembuatan sediaan sheet mask dari bahan dasar sari buah anggur dan Mengidentifikasi uji efektivitas kimia sediaan sheet mask dari bahan dasar sari buah anggur . Penelitian ini menggunakan metode eksperimen di laboratorium farmasi dengan pengujian uji oranoleptik, uji homogenitas, uji pH dengan konsentrasi (0%,2%,4%,6%), uji iritasi dengan 15 sukarelawan, uji kelembaban dengan 28 sukarelawan dan dilakukan selama 1 minggu. Berdasarkan hasil penelitian konsentrasi (0%,2%,4%,6%). Uji organoleptik semakin tinggi konsentrasi semakin berwarna ungu pucat berbau strawberry, uji homogenitas semua sediaan homogen, uji pH dengan konetrasi (0%: 6,73),(2%: 5,26),(4%: 4,83),(6%: 4,51), uji iritasi tidak terdapat kemerahan dan gatal pada 15 sukarelawan, uji kelembaban semakin tinggi konsentrasi semakin lembab kulit, (0%: 36,57),(2%: 37,57),(4%: 38,14),(6%: 40,57). Kesimpulan formulasi sediaan sheet mask sari buah anggur yaitu sari buah anggur bisa membuat kulit lembab.